Association of Cerebral Oxygenation During Exercise With Target Organ Damage in Middle-Aged Hypertensive and Normotensive Individuals. (24th March 2022) - Triantafyllou, Georgios A; Triantafyllou, Areti; Zafeiridis, Alexandros Savvas; Koletsos, Nikolaos; Zafeiridis, Andreas; Gkaliagkousi, Eugenia; Douma, Stella; Dipla, Konstantina
Abstract: Background: The brain is one of the main target organs affected by hypertension. Impaired cerebral oxygenation during exercise is an indicator of cerebral dysfunction. We aimed to investigate whether cerebral oxygenation during exercise correlates with subclinical markers of early target organ damage in a population of middle-aged, newly diagnosed hypertensive and healthy individuals. Methods: Carotid intima–media thickness (cIMT) was measured using ultrasound, arterial stiffness was estimated measuring the augmentation index and pulse wave velocity, and retinal vessel diameter was assessed via the central retinal-arteriolar and vein equivalent and retinal-arteriovenous ratio. Participants ( n = 93) performed a 3-minute isometric handgrip exercise. Cerebral prefrontal oxygenation was measured continuously using near infrared spectroscopy. The average exercise responses in oxygenated hemoglobin (O2 Hb), deoxygenated hemoglobin (HHb), and total hemoglobin (tHb) were assessed. Univariate analyses were performed; partial correlation was used to account for traditional cardiovascular risk factors to identify independent associations between cerebral-oxygenation indices and early markers of target organ damage. Results: Mean cIMT was negatively correlated with the average exercise response in cerebral oxygenation (rhoO2Hb = −0.348, P O2Hb = 0.001; rhotHb = −0.253, P thb = 0.02). Augmentation index was negatively correlated with cerebral oxygenation during exercise (rhoO2Hb = −0.374, P < 0.001; rhotHb = −0.332, P = 0.02), whereas no significant correlation was observed between pulse wave velocity and cerebral-oxygenation indices. In the adjusted analysis, cerebral oxygenation was correlated with central retinal arteriolar diameter (CRAE r = 0.233, P = 0.043). Conclusions: Our novel findings suggest that indices of lower cerebral oxygenation during a submaximal physical task are associated with markers of early, subclinical target organ damage, namely increased cIMT, arterial stiffness, and arteriolar retinal narrowing in newly diagnosed, untreated, hypertensive individuals. Graphical Abstract: